Tracking global change in ecosystem area: The Wetland Extent Trends index. (January 2016) - Dixon, M.J.R.; Loh, J.; Davidson, N.C.; Beltrame, C.; Freeman, R.; Walpole, M.
Abstract: We present a method for estimating broad trends in ecosystem area based on incomplete and heterogeneous data, developing a proof-of-concept for the first indicator of change in area of natural wetland, the Wetland Extent Trends (WET) index. We use a variation of the Living Planet Index method, which is used for measuring global trends in wild vertebrate species abundance. The analysis is based on a database containing 1100 wetland extent time-series records and the method identifies and addresses ecological and biogeographic biases in the dataset. Globally, the natural WET index, excluding human-made wetlands, declined by about 30% on average between 1970 and 2008. Declines varied between regions from about 50% in Europe to about 17% in Oceania over the same period. The WET index fills an important gap in the ecosystem coverage of global biodiversity indicators and can track changes related to a number of current international policy objectives. The same method could be applied to other datasets to create indicators for other ecosystems with incomplete global data. Highlights: The WET index is a proof-of-concept indicator of global change in wetland area. Between 1970 and 2008, natural wetlands declined globally on average by about 30%. Natural wetland extent declined across all five Ramsar regions assessed. Coastal wetlands declined globally on average more than inland wetlands.